Analysis of stability derivatives important to recovery from spin. Issue 2 (2nd April 2016) - Figat, Marcin; Goraj, Zdobysław
Abstract: This paper describes the numerical analysis of light aircraft stability derivatives in a wide range of angles of attack, important for recovery from spin. Stability derivatives versus angle of attack and sideslip were calculated using a CFD software, based on Euler equation combined with boundary layer equations. The analysis was performed up to the 40 deg of angle of attack and up to 25 deg of sideslip.